Recent Advances of Photoactive Near-Infrared Carbon Dots in Cancer Photodynamic Therapy - Jinxing Song; Xiaobo Gao; Mei Yang; Weiju Hao; Ding-Kun Ji (MDPI AG, 2023)
Photodynamic therapy (PDT) is a treatment that employs exogenously produced reactive oxygen species (ROS) to kill cancer cells. ROS are generated from the interaction of excited-state photosensitizers (PSs) or photosensitizing agents with molecular oxygen. Novel PSs with high ROS generation efficiency is essential and highly required for cancer photodynamic therapy. Carbon dots (CDs), the rising star of carbon-based nanomaterial family, have shown great potential in cancer PDT benefiting from their excellent photoactivity, luminescence properties, low price, and biocompatibility. In recent years, photoactive near-infrared CDs (PNCDs) have attracted increasing interest in this field due to their deep therapeutic tissue penetration, superior imaging performance, excellent photoactivity, and photostability. In this review, we review recent progress in the designs, fabrication, and applications of PNCDs in cancer PDT. We also provide insights of future directions in accelerating the clinical progress of PNCDs.